Understanding Consumer Characteristics in an Online Tourism Community in India (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Analysing customer perceptions is an important requirement not only for offline stores, but for online stores as well. Study of customer perceptions helps the company in understanding the requirements and expectations of the customers in a better way. This study is an extension of the researchers previous study of identifying antecedents of consumer trust for e-tourism companies in India. This study tries to explore the relationship between factors that build trust of the consumers on the online companies and their satisfaction level. Apart from studying the preferences and expectations of the consumers from e-tourism companies in India, the researcher has also tried to study the customer perceptions in context of online shopping in general. Data was collected by the researcher from 367 tourists (customers) who plan their tours online in Delhi NCR. Hypothesis testing has been done by using ANOVA and t-test. Findings of the study revealed that that amongst seven Consumer Trust dimensions, only Promotional deals and Price Competitiveness have a significant positive impact on Customer Satisfaction, whereas the impact of other five variables are not significant.